Reading in the developments of arbitration systems in Saudi Arabia and Malaysia: A comparative study - Abdul Wahab, Mohammad Khaled; bin Omar, Muhammad Naim (Journal of Economic, Administrative and Legal Sciences, 2020)
This research aims at a quick and effective solution to economic, commercial and other disputes. The Saudi legislator and the Malaysian legislature have taken measures that resulted in a series of regulations related to strengthening the arbitration system and law in both countries. Accordingly, the follower of the legislative systems and arbitration laws in Saudi Arabia and Malaysia will stand on the apparent progress and developments in the field of trade and economic development that (countries are witnessing) in all private and public sectors, with the use of appropriate mechanisms to resolve disputes, bearing in mind that the new Saudi system and the Malaysian law are based on the issue Arbitration to the UNCITRAL Model Law (which made it incumbent upon them to keep abreast of developments in line with the rules of Islamic law). The research used scientific methods, including: the analytical approach: to highlight and analyze the features of arbitration in the Saudi arbitration system and the Malaysian Arbitration Law. The inductive approach: in the extrapolation of the Saudi arbitration system and the Malaysian arbitration law. The comparative approach: In comparing the two systems, the Saudi arbitration system and the Malaysian arbitration law. The most important findings of the researchers, including: 1. Keeping pace with the new Saudi arbitration system and the Malaysian Arbitration Law for the concrete developments in the field of arbitration. 2. The Saudi system and the Malaysian law for arbitration recognize international control decisions and give them the executive formula that was not clearly contrary to the general international system. The researchers recommended wills, including: Developing data for everything related to the procedures and references required by the arbitration process, so that it relies on clear and accurate data so that it is within the reach of litigants who want to conduct the way of arbitration to resolve their disputes instead of the regular judiciary. Create a list of arbitrators specialized in various types of disputes and attract competencies in the field of Sharia and law without age or nationality as a barrier for them. Develop strategic plans for the establishment of a specialized body, whose task is to settle disputes in peace, and provide the necessary assistance to litigants to implement the award after its issuance.
Keywords: law; arbitration; Saudi Arabia; Malaysia; development; investment; judiciary